1990
DOI: 10.1111/j.1432-1033.1990.tb19346.x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Na+/K+ transport by the MgPO4 complex analogue Co(NH3)4PO4 leaves the Na+/Na+‐exchange reaction of the sodium pump unaltered and shifts its high‐affinity ATP‐binding site to a Na+‐like form

Abstract: Inactivation of Na+/K+‐ATPase activity by the MgPO4 complex analogue Co(NH3)4PO4 leads, in everted red blood cell vesicles, to the parallel inactivation of 22Na+/K+ flux and 86Rb+/Rb+ exchange, but leaves the 22Na+/Na+‐exchange activity and the uncoupled ATP‐supported 22Na+ transport unaffected. Furthermore, inactivation of purified Na+/K+‐ATPase by Co(NH3)4PO4 leads to a parallel decrease of the capacity of the [3H]ouabain receptor site, when binding was studied by the Mg2+/Pi‐supported pathway (ouabain‐enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…that at least 2 mol of phosphate can be incorporated into the catalytic ␣-subunit per mol of ouabain binding sites (14), is consistent with the coexistence of phosphorylated intermediates (E 1 P, E*P, and E 2 P (15)) at different places in an oligomeric enzyme. Also, the observations of phosphorylation from P i during Na ϩ -ATPase activity (16) and in an FITC-treated enzyme (10) are consistent with the possibility that Na ϩ /K ϩ -ATPase is phosphorylated from both ATP sites (12,17).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…that at least 2 mol of phosphate can be incorporated into the catalytic ␣-subunit per mol of ouabain binding sites (14), is consistent with the coexistence of phosphorylated intermediates (E 1 P, E*P, and E 2 P (15)) at different places in an oligomeric enzyme. Also, the observations of phosphorylation from P i during Na ϩ -ATPase activity (16) and in an FITC-treated enzyme (10) are consistent with the possibility that Na ϩ /K ϩ -ATPase is phosphorylated from both ATP sites (12,17).…”
supporting
confidence: 70%
“…Analysis (11,12), and Na ϩ -dependent phosphorylation (frontdoor phosphorylation) detects an activity of the E 1 ATP site (1,4,21). Interference by ErITC of the E 1 ATP site can be detected from the change of the Na ϩ -dependent phosphorylation of Na ϩ /K ϩ -ATPase by the chosen isothiocyanate in an enzyme whose E 2 ATP site had been blocked with Co(NH 3 ) 4 PO 4 .…”
Section: Kinetic Analysis Of the Inactivation Of K ϩ -Activated P-nitmentioning
confidence: 99%
“…lo), ADP/ATP exchange (Fig. 12), unchanged 22Na+/Naf exchange, and uncoupled "Na+ transport in C~(NH~)~PO,-treated everted red blood cells (which lack "Na+/K+ transport and "Rb+/ Rb+ exchange) [52], and the demonstration of two ATP-binding sites (Figs 13 -15). It is clear that the (a,P)z-diprotomeric structure has also to be proven more rigorously.…”
Section: Discussionmentioning
confidence: 95%
“…Similar data have been reported for modification of the low-affinity ATP-binding site by Co(NH3),ATP [23 -251. Additionally, we recently showed that Co(NH3),P04 inactivates "Na+/K+ transport and "Rb+/Rb+ exchange but not "Na+/K+ exchange nor uncoupled 22Na+ transport in everted erythrocytes [52]. Since Co(NH3),P04 and Co(NH3),ATP, but not CrATP, differentiate between the partial activities in a similar way, it is likely that the chromium and Co(NH,), complexes per se differentiate between El and Ez, and not the nature of the ligand (ATP or phosphate).…”
Section: Discussionmentioning
confidence: 97%
“…Na + -dependent phosphorylation at the EiATP site [11] and K+-activated phosphatase activity at the E 2 ATP site [12,13]. Therefore, we performed several experiments to study the effect of NBD-C1 on the enzyme with specifically blocked EiATP-(FITC-pretreated) or E 2 ATP-binding site (Co(NH 3 ) 4 P0 4 -pretreated).…”
Section: Introductionmentioning
confidence: 99%